2018
DOI: 10.5606/archrheumatol.2018.6608
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficiency Between Corticosteroid and Platelet Rich Plasma Injection Therapies in Patients With Knee Osteoarthritis

Abstract: Objectives: This study aims to assess whether platelet rich plasma (PRP) is an effective treatment for knee osteoarthritis (OA), and compare its efficiency with corticosteroid treatment in terms of pain control, physical function, and quality of life. Patients and methods: The study included 50 patients (4 males, 46 females; mean age 61.6±6.9 years; range 50 to 75 years) who were diagnosed as grade 3 knee OA. Patients were randomized into three groups as corticosteroid group (receiving one corticosteroid injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 17 publications
4
65
1
Order By: Relevance
“…Follow-up ranged from 6 months up to 2 years; thus, for such a large group as OA, heterogeneity will be too high due to our inability to compare outcomes at the same time point. Twenty-eight studies compared PRP versus control groups [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]73,[76][77][78][79]82,83,[86][87][88][89]91], five studies compared PRP with the addition of another substance (MSC or HA) versus the control groups [74,79,81,91], six studies compared multiple injections of PRP [54,59,80,[85][86][87], three studies compared PRGF-Endoret versus control groups [71,75,90], two studies compared autologous conditioned plasma (ACP) versus control groups [72,84], and one study compared intraosseous injection versus intra-articular injection versus the control group [67]. In twenty-three studies, HA …”
Section: Osteoarthritismentioning
confidence: 99%
See 4 more Smart Citations
“…Follow-up ranged from 6 months up to 2 years; thus, for such a large group as OA, heterogeneity will be too high due to our inability to compare outcomes at the same time point. Twenty-eight studies compared PRP versus control groups [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]73,[76][77][78][79]82,83,[86][87][88][89]91], five studies compared PRP with the addition of another substance (MSC or HA) versus the control groups [74,79,81,91], six studies compared multiple injections of PRP [54,59,80,[85][86][87], three studies compared PRGF-Endoret versus control groups [71,75,90], two studies compared autologous conditioned plasma (ACP) versus control groups [72,84], and one study compared intraosseous injection versus intra-articular injection versus the control group [67]. In twenty-three studies, HA …”
Section: Osteoarthritismentioning
confidence: 99%
“…Twenty-three studies reported pain via the VAS comparing PRP versus placebo [54][55][56][57]69,86], corticosteroids [58,59,77] or HA [54,[60][61][62][63][65][66][67][68][69][70][71][76][77][78][79]87] (Figure 10). Placebo and HA subgroups showed significant differences in favor of PRP (p < 0.00001), despite the steroid subgroup showing non-significant differences in favor of PRP (p = 0.23).…”
Section: Osteoarthritismentioning
confidence: 99%
See 3 more Smart Citations